Comparative Study of Polygamous Marriage Law in Indonesia and Tunisia - Fathor Rozy; Mohammad Ainul Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Polygamy is a practice recognized by law in some countries, although its implementation often sparks debate from social, cultural, and legal perspectives. In Indonesia, polygamy is regulated by Law Number 1 of 1974 on Marriage, which imposes certain limits and strict requirements, while in Tunisia, polygamy has been explicitly prohibited since the enactment of the Code du Statut Personnel (CSP) in 1956. This study aims to examine the regulations, legal provisions, and the social and legal impacts of polygamy practices in these two countries. Using a qualitative method with a normative approach, this research explores the comparison of legal foundations, government policies, and the implementation of regulations related to polygamy, identifying the differences and similarities. The results of this study show that Indonesia and Tunisia have different approaches to polygamy, with Indonesia allowing polygamy within certain limits, while Tunisia strictly prohibits it. Both countries seek to protect women's rights in the context of marriage, although the implementation of these policies faces various social and cultural challenges.